USTADZ PROFESSIONAL COMPETENCE IN IMPROVING HR QUALITY MANAGEMENT - Baidawi, Achmad Naufal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze the quality management of human resources in increasing the professional competence of Ustadz at Pondok Pesantren Nurul Jadid Paiton Probolinggo. This study uses descriptive statistical data analysis and qualitative analysis. Sources of data come from observation, interviews, documentation, and Library Research. The results of the study show that quality management of human resources (HR) in improving the professional competence of ustadz at Nurul Jadid Islamic Boarding School has been implemented in recruitment planning by conducting needs analysis, calling and selecting before starting teaching. Pondok Pesantren Nurul Jadid also places ustadz according to their scientific fields, and educational development is carried out by including training and providing opportunities to continue their education at a higher level.